Kegiatan Pengabdian Kepada Masyarakat- Skrining Penyakit Tidak Menular pada Usia Produktif di SMA ST. Yoseph, Cakung, Jakarta Timur - Alexander Halim Santoso; Steven Hizkia Licius; Andrew Philo; Ryan Dafano Putra Mahendri (Fakultas Teknik Universitas Maritim AMNI Semarang, 2025)
Non-communicable diseases (NCDs) are a global health challenge, especially in low- and middle-income countries. Early identification of NCDs in the productive age group is very important considering the contribution of the productive age group to the national workforce and its impact on the health of future generations. This community service activity aims to increase awareness and participation in school-based non-communicable disease screening programs, especially at St. Yoseph High School, East Jakarta. The implementation of screening activities includes anthropometric examinations, blood pressure, blood sugar, and short interviews. Students with unhealthy lifestyles, such as lack of physical activity and unbalanced diets, are at high risk of developing non-communicable diseases. This activity encourages public awareness of the importance of maintaining health to prevent non-communicable diseases. This can reduce the global health burden and the economic burden for advanced disease care. Thus, this activity can improve the quality of life of the productive age population in the future.